Citizen science can improve conservation science, natural resource management, and environmental protection. (April 2017) - McKinley, Duncan C.; Miller-Rushing, Abe J.; Ballard, Heidi L.; Bonney, Rick; Brown, Hutch; Cook-Patton, Susan C.; Evans, Daniel M.; French, Rebecca A.; Parrish, Julia K.; Phillips, Tina B.; Ryan, Sean F.; Shanley, Lea A.; et al.
Abstract: Citizen science has advanced science for hundreds of years, contributed to many peer-reviewed articles, and informed land management decisions and policies across the United States. Over the last 10 years, citizen science has grown immensely in the United States and many other countries. Here, we show how citizen science is a powerful tool for tackling many of the challenges faced in the field of conservation biology. We describe the two interwoven paths by which citizen science can improve conservation efforts, natural resource management, and environmental protection. The first path includes building scientific knowledge, while the other path involves informing policy and encouraging public action. We explore how citizen science is currently used and describe the investments needed to create a citizen science program. We find that: 1. Citizen science already contributes substantially to many domains of science, including conservation, natural resource, and environmental science. Citizen science informs natural resource management, environmental protection, and policymaking and fosters public input and engagement. 2. Many types of projects can benefit from citizen science, but one must be careful to match the needs for science and public involvement with the right type of citizen science project and the right method of public participation. 3. Citizen science is a rigorous process of scientific discovery, indistinguishable from conventional science apart from the participation of volunteers. When properly designed, carried out, and evaluated, citizen science can provide sound science, efficiently generate high-quality data, and help solve problems. Highlights: Citizen science can improve conservation efforts by building scientific knowledge. It can also improve conservation efforts by encouraging public action. Project design must match the needs for science and public involvement. Citizen science is a powerful tool for tackling conservation challenges.